Outcomes of simultaneous high tibial osteotomy and anterior cruciate ligament reconstruction in anterior cruciate ligament deficient knee with osteoarthritis - Cheng Jin (BMC Musculoskeletal Disorders, 2018)
Abstract Background We aimed to evaluate clinical and radiological results after simultaneous open-wedge high tibial osteotomy (HTO) and anterior cruciate ligament (ACL) reconstruction in patients with ACL deficiency combined with medial uni-compartmental osteoarthritis (OA) and varus deformity. Methods This retrospective study was performed using data collected from 2005 to 2011 on a total of 24 patients who were diagnosed with ACL injury and medial unicompartmental OA with varus deformity, and who subsequently underwent simultaneous open-wedge HTO and arthroscopic ACL reconstruction. The mean follow-up duration was 5.2 years. For clinical outcomes, we evaluated Lysholm score, Tegner activity score, range of motion, Lachmann test, and pivot-shift test, and for radiological outcomes, we evaluated the degree of varus deformity, progression of medial OA, tibial posterior slope, anterior instability, and postoperative complication. Results There were no limitations in range of motion found in any cases. Three patients showed progressive osteoarthritis on the medial compartment. The mechanical femorotibial angle was significantly corrected from varus 7.0 degrees to valgus 1.2 degrees, and the tibial posterior slope was not significantly changed. The Lysholm and Tegner activity scores were significantly improved after surgery (from 58 to 94 points on the Lysholm scale and from 4.0 to 5.3 points on the Tegner activity scale). Although the Lachman test and the pivot-shift test showed significant improvements after surgery, instability greater than Gr II was observed in three patients on the Lachman test and in four patients on the pivot-shift test. The side-to-side difference improved from 9.6 mm to 4.2 mm postoperatively as assessed using a Telos® arthrometer. There were no cases of nonunion or fixation loss. Conclusions Simultaneous open-wedge HTO and ACL reconstruction in patients with ACL injury with medial compartmental OA showed satisfactory functional outcomes and postoperative activity level scores. However, some patients showed residual instability and progression of OA.